Reasonable restrictions on the freedom of fishing in high seas marine protected areas from an international law perspective: an analysis - Wang, Yong; Pan, Xin (Frontiers in Marine Science, 2023)
With the development of marine protected areas (MPAs) on the high seas in the international community and the Biodiversity Beyond National Jurisdiction, an international agreement for the protection of water bodies beyond any national control, how to reasonably restrict the freedom of fishing in MPAs on the high seas has become a controversial issue in theory and in practice. The fishing-restriction measures stipulated in international documents represented by the United Nations Convention on the Law of the Sea are too general. In addition, some treaties do not address certain issues of restricting fishing methods by non-contracting parties; therefore, those treaties are limited. Examining the fishing practices of the four high seas MPAs that have been established by the international community reveals the establishment several reasonable fishing restrictions; however, some shortcomings are evident. From the perspective of international law, it is important to improve the principle of reasonably restricting the freedom of fishing in MPAs on the high seas based on practice and positive law while proceeding steadily. Moreover, restriction measures cannot be too broad or narrow. Specifically, we should continue to develop mechanisms such as exceptions, requirements for inspection, ways of restricting fishing, advocacy provisions for non-parties and measures to strengthen international information exchange.